PROGRAM LITERASI UNTUK MENINGKATKAN MINAT BACA SISWA DI SMP IMANUEL PONDOK GEDE - Robinson Sihombing (Haga : Jurnal Pengabdian Kepada Masyarakat, 2023)
The Literacy Program to Increase Students' Reading Interest at SMP Imanuel Pondok Gede aims to develop a reading culture among students through a series of innovative and enjoyable activities. In the current digital era, students' reading interest tends to decline, necessitating effective strategies to encourage their engagement with books. This program includes teacher training in engaging teaching methods, the provision of varied reading materials, and activities such as book clubs and reading competitions. Through observation and evaluation, this program is expected to enhance students' reading interest and strengthen their literacy skills. The anticipated outcome is an increase in reading frequency among students, as well as their ability to understand and analyze texts. Thus, this program not only contributes to improving literacy but also helps shape students into more critical and creative individuals.